Hoy hubiera preferido no encontrarme a mi misma - Müller, Herta, 1953-; Solar, Juan José del; Müller, Herta, 1953- (Madrid : Ediciones Siruela, 2012)
"I've been summoned. Thursday, ten sharp." Thus begins one day in the life of a young clothing-factory worker during Ceaucescu's totalitarian regime. She has been questioned before; this time, she believes, will be worse. Her crime? Sewing notes into the linings of men's suits bound for Italy. "Marry me," the notes say, with her name and address. Anything to get out of the country. As she rides the tram to her interrogation, her thoughts stray to her friend Lilli, shot trying to flee to Hungary, to her grandparents, deported after her first husband informed on them, to Major Albu, her interrogator, who begins each session with a wet kiss on her fingers, and to Paul, her lover, her one source of trust, despite his constant drunkenness. In her distraction, she misses her stop to find herself on an unfamiliar street. And what she discovers there makes her fear of the appointment pale by comparison.
Online resource; title from ePub title page (Digitalia, viewed April 8, 2016)
Keywords: Romania -- Social conditions -- Fiction; Women clothing workers -- Romania -- Fiction; Factories -- Romania -- Fiction; Women -- Romania -- Fiction; Communism -- Romania -- Fiction; Political persecution -- Romania -- Fiction; Electronic books